Endovascular Treatment of Aorta-Iliac Aneurysms with a Flared Iliac Limb - Duvnjak, Stevo; Balezantis, Tomas (International Journal of Angiology, 2019)
Endovascular abdominal aneurysm repair (EVAR) relies on the quality of the proximal and distal landing zone. Reinterventions are higher in patients with suboptimal landing zone. The study aimed to evaluate reintervention rate after endovascular treatment of an aorta-iliac aneurysm using the flared iliac limbs.The retrospective study included 179 patients treated with EVAR at a single university hospital institution from January 2011 to January 2014 of which 75 patients (42%) were treated with flared iliac limb stent graft and 104 patients (58%) were treated with a nonflared iliac limb stent graft. There were 165 male patients (92%), mean age was 75.8 ± 6.6 years.Thirty-six patients underwent secondary treatment accounting for overall reintervention rate of 20%. Endoleak type 1b occurred in 13 patients (7%), followed by endoleak type 1a in six patients (3%). Endoleak type 2 occurred in seven patients (4%) requiring the treatment due to abdominal aortic aneurysm (AAA) enlargement, endoleak type 3 in three patients (2%), and leg stent graft thrombosis in seven patients (4%). In 143 patients (80%), there were no secondary interventions during the follow-up period. Reintervention due to endoleak type 1b was statistically significantly higher in a flared iliac limb group (p < 0.02) with the rate of 7.2% compared with 1.9% rate in nonflared iliac limb group. The mean follow-up was 44.3 ± 20.4. Overall mortality was 33%.Flared iliac limb with a distal diameter of ≥ 20 mm, show a higher rate of iliac limb reintervention in a follow-up period due to endoleak type 1b.
Keywords: endoleak; abdominal aortic aneurysm; endovascular abdominal aneurysm repair; common iliac artery